Evolución de los recursos del SGP y su incidencia en los niveles de educación en los municipios de la provincia del Tequendama 2010-2018 (2021)
The importance of education as an engine of social change and generator of opportunities for a better quality of life has been supported by economist theorists such as Solow, Lucas or Stiglitz, and in turn they highlight its importance to the very economy of a country under the concept of human capital. Whether for purely economic or social reasons, the State must be the guarantor that this asset is loaned to all its inhabitants as dictated by the constitution. Given this, the Nation created in 2001 the General Participation System, whose main function is fiscal decentralization and be the main actor of public spending in the country, focusing on health, basic sanitation and education in those territories that have fewer opportunities. to cover these factors themselves.